Clinocera Meigen of Thailand (Diptera: Empididae: Clinocerinae) - Sinclair, Bradley J.; Plant, Adrian R. (Zootaxa, 2022)
Eight new species of Clinocera Meigen from Thailand are described and illustrated (C. abbreviata sp. nov., C. areeluckorum sp. nov., C. courtneyi sp. nov., C. gracilis sp. nov., C. rostrata sp. nov., C. spatulata sp. nov., C. srisukai sp. nov., C. univittata sp. nov.). A key to Thailand species is provided. Distributions, phenology and biogeography are discussed. Several Thailand species also occur in Bhutan, China and Vietnam.